Looking Through the Wrong End of the Telescope: The Japanese Judicial Response to Steel Partners, Murakami, and Horie - Stephen Givens (Washington University Law Review, 2011)
The Article discusses the “Bulldog Sauce” case of the Japanese Supreme Court which addresses corporate laws. It outlines the judicial efforts of the Japanese Supreme Court to utilize defensive techniques against corporate raiders. It highlights the Article 109 and 247 of the Company Law which have been considered by the Japanese Supreme Court in the decision making.
Keywords: Consolidation & merger of corporations -- Japan; Poison pills (Securities); Japan. Daishin' in